Glycoursodeoxycholic acid regulates bile acids level and alters gut microbiota and glycolipid metabolism to attenuate diabetes - Bingting Chen; Yu Bai; Fenglian Tong; Junlin Yan; Rui Zhang; Yewei Zhong; Huiwen Tan; Xiaoli Ma (Gut Microbes, 2023)
ABSTRACTAccumulating evidence suggests that the bile acid regulates type 2 diabetes mellitus (T2DM) through gut microbiota-host interactions. However, the mechanisms underlying such interactions have been unclear. Here, we found that glycoursodeoxycholic acid (GUDCA) positively regulates gut microbiota by altering bile acid metabolism. GUDCA in mice resulted in higher taurolithocholic acid (TLCA) level and Bacteroides vulgatus abundance. Together, these changes resulted in the activation of the adipose G-protein-coupled bile acid receptor, GPBAR1 (TGR5) and upregulated expression of uncoupling protein UCP-1, resulting in elevation of white adipose tissue thermogenesis. The anti-T2DM effects of GUDCA are linked with the regulation of the bile acid and gut microbiota composition. This study suggests that altering bile acid metabolism, modifying the gut microbiota may be of value for the treatment of T2DM.